2012
DOI: 10.7341/2012841
|View full text |Cite
|
Sign up to set email alerts
|

Job Design and Innovative Work Behavior: One Size Does Not Fit All Types of Employees

Abstract: As innovative employees become imperative for an organizations' success, research identified job design as a crucial variable in promoting innovative work behavior (IWB) (Hammond et al., 2011). Using the Job Demands-Resources (JD-R) model of Bakker & Demerouti (2007) Broeck et al., 2010) , this article contributes to the literature as it uses recent insights on the distinction between job challenges and job hindrances (Van den

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
(53 reference statements)
2
48
0
2
Order By: Relevance
“…Evidence of this effect has been found by various researchers including De Spiegelaere et al (2012) and Ramamoorthy et al (2005).…”
Section: Hrm and Iwbmentioning
confidence: 69%
See 1 more Smart Citation
“…Evidence of this effect has been found by various researchers including De Spiegelaere et al (2012) and Ramamoorthy et al (2005).…”
Section: Hrm and Iwbmentioning
confidence: 69%
“…Both hypotheses are based on fear, which in general would not be seen as a strong motivation for IWB. De Spiegelaere et al (2012) studied insecurity over job content: that employees fear that the content of their work might change, rather than employment insecurity (fear of losing one's job). In this respect, they were able to show evidence for both the positive and negative hypotheses of the influence of job security on IWB.…”
Section: Iwbmentioning
confidence: 99%
“…Although the JD-R theory states that job resources result in positive work outcomes, and that it is job demands that result in negative work outcomes, other researchers have shown that job demands are positively associated with IWB (De Spiegelaere, Van Guys, & Van Hootegem, 2012;Janssen, 2000;Wu, Parker, & de Jong, 2014). Here, job demands can be understood as challenges that motivate employees to seek new ways to deal with their work (De Spiegelaere et al, 2012;Wu et al, 2014). Our production employees may have been 'made too comfortable' because they were provided with multiple job resources but no such job demands (Veenendaal & Bondarouk, 2015, p. 154).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Recientemente, ha surgido el concepto de comportamiento innovador en el trabajo (Innovative Work Behaviour "IWB") para referirse a los empleados que se implican en actividades innovadoras (De Spiegelaere et al, 2012). El comportamiento innovador en el trabajo aglutina una serie de actividades dirigidas hacia el reconocimiento, desarrollo, modificación, adopción e implementación de ideas (Van de Ven, 1986;Scott y Bruce, 1994).…”
Section: Innovación Y Comportamiento Innovador En El Trabajounclassified
“…Los indicadores se muestran agrupados y clasificados según la dimensión a la que pertenecen, de acuerdo con el Modelo FINCODA de competencia de innovación. (Watts et al, 2012;Scott & Bruce, 1994) Generate original solutions for problems or to opportunities (De Spiegelaere et al, 2012;Janssen, 2000) CRITICAL THINKING Evaluate the advantages and disadvantages of actions or ideas (Watts et al, 2012;Kleysen & Street, 2001;Janssen, 2000) Develop and experiment with new ways of problem solving (Choi, 2004) (De Spiegelaere et al, 2012;Kleysen & Street, 2001) Use an action-based approach: develop goals, collect information, make plans for executing them (Patterson et al, 2009;De Spiegelaere et al, 2012) TEAMWORK Interact effectively with others to facilitate the gathering, integrating and conveying of information in many forms (Watts et al, 2012;Choi, 2004) Identify sources of conflict between oneself and others, or among other people, and to take steps to overcome disharmony (Berdrow & Evers, 2010;Watts et al, 2012 ) NETWORKING Identify the appropriate decision makers and stakeholders who have the power to make a difference (Watts et al, 2012) Build relationships outside the team/organization (Ferris et al, 2005) …”
Section: Figura 1 © Fincoda Upv-see-csp Team (2016) Innovation Compmentioning
confidence: 99%